2014
DOI: 10.1002/nau.22627
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa of murine detrusor impairs β2-adrenoceptor-mediated relaxation

Abstract: The mucosa of mouse detrusor strips impairs KCl-induced force development and reduces the sensitivity to β-AR-induced relaxation. The relaxing response to (-)-isoprenaline as well as the mucosa effect thereupon are mainly mediated by β2 -ARs. A minor involvement of β3 -ARs becomes apparent particularly at high (-)-isoprenaline concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 32 publications
3
5
1
Order By: Relevance
“…These findings confirm our previous observations ( Wuest et al, 2009 ; Propping et al, 2013 , 2015a ) that β 2 -ARs are the major β-AR subtype mediating relaxation in WT detrusor strips. However, given the low affinity of L748,337 for murine β 3 -ARs ( Cernecka et al, 2014 ), the concentration of 100 nM L748,337 may not have been sufficient to block murine β 3 -AR.…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…These findings confirm our previous observations ( Wuest et al, 2009 ; Propping et al, 2013 , 2015a ) that β 2 -ARs are the major β-AR subtype mediating relaxation in WT detrusor strips. However, given the low affinity of L748,337 for murine β 3 -ARs ( Cernecka et al, 2014 ), the concentration of 100 nM L748,337 may not have been sufficient to block murine β 3 -AR.…”
Section: Resultssupporting
confidence: 93%
“…Subtypes involved in mouse bladder are controversial. While we have found that detrusor relaxation is mediated via β 2 -AR ( Wuest et al, 2009 ; Propping et al, 2015a ), other authors have suggested β 3 -ARs as the relevant subtype ( Deba et al, 2009 ). Some of this discrepancy may be due to different experimental conditions, but another major issue is that the various drugs employed may actually not exhibit the assumed β-AR subtype selectivity ( Cernecka et al, 2014 ).…”
Section: Introductioncontrasting
confidence: 72%
See 2 more Smart Citations
“…We used atenolol (Bogaert, Rosseel, & Lefebvre, 1984;Prachi, Komal, & Priti, 2017), ICI 118,551 (Baker, 2010;Propping, Newe, Kaumann, Wirth, & Ravens, 2015) and propranolol (Hoffmann, Leitz, Oberdorf-Maass, Lohse, & Klotz, 2004;Tan & Yang, 2016;Zhang et al, 2011b) as the selective β 1 -AR, selective β 2 -AR and non-selective β-AR antagonists, respectively. The doses of the β-AR antagonists were selected according to our previous experimental data, which were shown to be the optimal doses for stable monitoring of haemodynamics (Zhang et al, 2011a(Zhang et al, , 2012.…”
Section: Changes In Haemodynamic Indexesmentioning
confidence: 99%